Gaya Belajar Mahasiswa Thailand di Universitas Islam Riau - Mukhlis, Muhammad (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
Learning styles are the ways, attitudes, and habits undertaken by students to gain comfort in learning. In this case, the researcher analyzed the foreign students’ learning style from Thailand who are studying at the Islamic University of Riau. The result of study showed that foreign students’ learning style from Thailand tended to use Kinesthetic learning style. This was based on research findings, learning style that has the highest value of kinestetik with an average of 84.6%, followed by an auditory learning style with an average of 76.9% and then visual learning style with an average of 61.5 %. As the findings in research are: First, for visual learning style students prefered to use the media in the lecture process. They were more able to concentrate when the lecturer explains the lecture material when looking at the face. Students could not memorize the material while listening to music. Students understood the material written on the board rather than read more quickly. Second, for auditory learning style, students prefered their lecturers by using lecture method. Students more easily remembered well the lecture material during the discussion. Students will lose concentration, when they heard a noise. Students prefered to discuss with friends if they find problems learning. Third, for students' kinesthetic learning styles along with. Students were more interested in lectures that are in practice. Students memorized the material while walking more dominant. when studying students could not read quickly. The findings could certainly be an input for educators in order to absorb, organize, and suit the learning strategies with learning styles, so as to show good learning outcomes and will be in accordance with lecture objectives